Bidirectional Photomodulation of Surface Tension in Langmuir Films. (14th December 2016) - Cheng, Jinling; Štacko, Peter; Rudolf, Petra; Gengler, Régis Y. N.; Feringa, Ben L.
Abstract: Switching systems operating in a cooperative manner capable of converting light energy into mechanical motion are of great interest for optical devices, data storage, nanoscale energy converters and molecular sensing. Herein, photoswitchable monolayers were formed at the air–water interface from either a pure bis(thiaxanthylidene)‐based photoswitchable amphiphile or from a mixture of the photoswitchable amphiphile with a conventional lipid dipalmitoylphosphatidylcholine (DPPC). Efficient photoisomerization of the anti ‐folded to syn ‐folded geometry of the amphiphile's central core induces changes in the surface pressure in either direction, depending on the initial molecular density. Additionally, the switching behavior can be regulated in the presence of DPPC, which influences the packing of the molecules, thereby controlling the transformation upon irradiation. Bis(thiaxanthylidene)‐based photoswitchable monolayers provide a promising system to explore cooperativity and amplification of motion. Abstract : Photoschaltbare Monoschichten werden von einem Bis(thiaxanthyliden)‐basierten photoschaltbaren Amphiphil oder von einer Mischung des Amphiphils mit dem gewöhnlichen Lipid Dipalmitoylphosphatidylcholin an Luft‐Wasser‐Grenzflächen gebildet. Die effiziente Photoisomerisierung der anti ‐gefalteten in die syn ‐gefaltete Geometrie des Amphiphilkerns bewirkt eine Änderung des Oberflächendrucks.